2015
DOI: 10.1111/aos.12721
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of combined bevacizumab/targeted photocoagulation vs bevacizumab alone for macular oedema in ischaemic branch retinal vein occlusions

Abstract: ABSTRACT.Purpose: To investigate whether targeted retinal photocoagulation (TRP) of peripheral non-perfused areas (NPAs) could prevent the recurrence of macular oedema (ME) due to branch retinal vein occlusion (BRVO) after intravitreal bevacizumab injection (IVB). Methods: Eyes received 1.25 mg IVB only (IVB group) or combined with TRP (IVB + TRP group) of NPAs, more than 5 disc areas identified by fluorescein angiography in the patients with ME secondary to BRVO. Best-corrected visual acuity (BCVA) and centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
0
25
0
3
Order By: Relevance
“…7 Furthermore, our previous study showed that when compared with anti-VEGF therapy alone, targeting retinal photocoagulation to NPAs reduces the severity of macular edema recurrence after anti-VEGF therapy. 8 However, no reports have used an animal RVO model to investigate whether photocoagulation of retinal NPAs suppresses the expression of VEGF. Therefore, the aim of this study was to evaluate whether the laser photocoagulation of NPAs of the retina suppresses ocular VEGF expression in a rabbit RVO model.…”
mentioning
confidence: 99%
“…7 Furthermore, our previous study showed that when compared with anti-VEGF therapy alone, targeting retinal photocoagulation to NPAs reduces the severity of macular edema recurrence after anti-VEGF therapy. 8 However, no reports have used an animal RVO model to investigate whether photocoagulation of retinal NPAs suppresses the expression of VEGF. Therefore, the aim of this study was to evaluate whether the laser photocoagulation of NPAs of the retina suppresses ocular VEGF expression in a rabbit RVO model.…”
mentioning
confidence: 99%
“…Interestingly, they also observed that untreated NP anterior to the globe equator was significantly associated with ME. Tomomatsu et al 16 and Singer et al 17 reported that TRP to these NP areas following intravitreal bevacizumab injection reduced the severity of recurrent ME compared with intravitreal bevacizumab injection alone.…”
Section: Discussionmentioning
confidence: 99%
“…Tomomatsu et al [22] reported that laser photocoagulation for peripheral NPAs prevented the recurrence of ME in BRVO. However, Campochiaro et al [23] reported that scatter photocoagulation did not reduce macular edema in BRVO.…”
Section: Discussionmentioning
confidence: 99%